Facile synthesis of silicon films by photosintering as anode materials for lithium-ion batteries - Chen, Wei; Jiang, Nan; Fan, Zhongli; Dhanabalan, Abirami; Chen, Chunhui; Li, Yunjun; Yang, Mohshi; Wang, Chunlei (Journal of power sources, 2012)
The silicon films as anode materials for lithium-ion batteries were fabricated by the cost-effective, high-throughput photosintering process. The thinner Si film (1.3 μm) exhibited larger storage capacity and better cyclability compared to the thicker one (4.2 μm) due to the close contact of the fused silicon nanoparticles with the substrate. Moreover, the addition of silver nanoparticles improved the conductivity of silicon film and facilitated the amorphous phase formation, resulting in enhanced capacity and cyclability. The photosintering approach highlights the advantage in the flexible and practicable manufacture and shows the promising prospects for developing high-performance Si-based anode materials. [Display omitted] ► Silicon films were fabricated by photosintering process. ► As-prepared silicon films were used as anode materials of lithium-ion batteries. ► The thinner Si film exhibited larger storage capacity and better cyclability. ► The addition of silver nanoparticles further improved the battery performance.